Shah Ismail Khatai in the Historical Sources of the Ahl-i Haqq Alevis - Baharlu, İlgar (Journal of Alevism-Bektashism Studies, 2024)
Since its establishment, the Ardabil Sufi lodge has attracted the people of Anatolia, becoming a sacred space for them. Those who gathered around this lodge, by dedicating themselves to the Safavid guides, eventually facilitated the emergence of a Kızılbaş Alevi state, leaving their mark on history as Kızılbaş Alevis. The Kızılbaşiye State1 was officially founded by Shah Ismail Hatayi, who was a descendant of this dynasty. However, Shah Ismail Hatayi is not only regarded as the founder of a state among Alevi communities living in regions such as Anatolia, the Balkans, and Iraq, but also as a perfect guide (mürşid-i kâmil) and a great poet. In fact, in the eyes of these Alevi communities, Hatayi is considered more as a charismatic spiritual leader than a political figure. In the tales among these Alevi groups, the saying “No cems is held without Hatayi” reflects the importance of Hatayi, showing that his name must be invoked for the ritual to be complete. In addition to these regions, Iran, which has a significant Alevi population, is one of the lands with a high concentration of Alevi followers. Contemporary Iran, a vast country, is home to the largest Alevi population after Turkey, under the broader term “Ehl-i Hak.” For centuries, the Ehl-i Hak Alevis have spread across this region and managed to preserve and live their belief system within closed communities. The Ehl-i Hak dynasties2 consist of various ethnic groups such as Turks, Kurds, Lor, and Lek. These communities have maintained their beliefs by preserving a strong oral culture as well as written historical sources. When examining the sources of these Alevi groups, one can observe the belief system formed around saints and sacred figures. In this context, the place of Shah Ismail Hatayi in the Ehl-i Hak groups, which hold a significant place in Anatolian Alevism, is a matter of interest. In fact, when considering the history of the Middle and Early Modern periods of Iran, one may conclude that these two countries share great socio-cultural, political, and economic similarities. Therefore, it is reasonable to assume that the Ehl-i Hak Alevis, as adherents of a Sufi and esoteric belief, are not historically different from the Alevis of Anatolia and the Balkans. Particularly, with the rise of the Kızılbaş state in the context of Safavid history, it is natural for the Ehl-i Hak to also have their place in history, just as the Alevi communities in Anatolia and the Balkans did. However, the position of Hatayi among the Ehl-i Hak Alevis in Iran, and their view of Shah Hatayi, has not been thoroughly discussed in historical and belief-based sources. In this regard, it can be seen from the sources accepted among the Ehl-i Hak Alevis that Shah Ismail Hatayi holds an important place. According to the sources available in this study, Hatayi is regarded as a sacred figure of this belief system among the Ehl-i Hak dynasties. Moreover, in the verses of the Ehl-i Hak and the words of the lovers of Hak (the divine) (poems/songs), this belief system’s sacred figures are generally mentioned, and Hatayi is recognized as a saint. In Ehl-i Hak sources, Shah Ismail Hatayi is depicted as a figure who emerged at a certain period to spread the path of God.